Um estudo sobre Podcasteros de Game of Thrones - Murta, Cíntia Maria Gomes (Universidade Federal de São Carlos, 2016)
Known as the Age of Conversation, the present time is marked by horizontal communication, based on connectivity between people and their networking. This setting reconfigures the media landscape from new conversation environments such as podcast. The present dissertationinvestigates the contents of Podcasteros produced by a network of Brazilian fans of the television series Game of Thrones (HBO, United States, 2011-present). The understanding of the series, the strategies used by HBO and content produced by fans aims to discuss a business model based on participatory culture that prioritizes dialogue not always friendly between producers and fans. At first, the series will be presented whose complex narrative universe unfolds through multiple plots, characters and settings - which leads the viewer to search for information on other platforms to understand not only what is narrated as sharing, networking, their impressions and versions of history. Observe the discursive network of fans around the series, therefore, requires the understanding that it is formed from ephemeral and temporary ties and marked by discursive diversity of its members. Finally, the Podcasteros content analysis will be addressed. The methodology proposed merges content analysis and netnography and is an investigative journey that seeks to meet the specific characteristics of the object and its sound nature in the context of discursive networks of fans and their dialogic practices.
Keywords: Redes de fãs; Podcasteros; Game of Thrones; Fandom; LINGUISTICA, LETRAS E ARTES